Performance Of A Hydraulic Ram Pump - Chin, Han Chuan (Universiti Sains Malaysia, 2018)
Hydraulic ram pump is a renewable energy device used to pump water using potential energy of falling water based on water hammer effect. The changes in supply head, delivery head and air vessel geometry of hydraulic ram pump will affect its performance. The effects of these factors on the pump performance were studied experimentally. Several sets of experiments were conducted under supply heads of 1.0m, 1.5m and 2.0m, delivery heads from 2.0m to 7.5m and air vessels with volume of 0.515L, 1.030L, 1.544L, 2.059L and 2.574L. The results showed that the increase in supply head improved the pump performance whereas the increase in delivery head caused a decrease in the performance. At supply head of 1.0m, hydraulic ram pump operated at volumetric efficiency of 0.855% to 6.022% at delivery head of 2.0m to 5.5m and air vessel with 1.030L had the overall best performance. At supply head of 1.5m, hydraulic ram pump operated at volumetric efficiency of 2.550 % to 5.925% at delivery head of 2.0m to 5.5m and air vessel with 1.544L had the overall best performance. At supply head of 2.0m, hydraulic ram pump operated at volumetric efficiency of 1.064% to 2.790% at delivery head of 4.0m to 7.5m and air vessel with 1.544L had the overall best performance. Besides, hydraulic ram pump with smaller air vessel performed better in high delivery heads but bigger air vessel was required when the supply head increased. The findings of this research also provide a guideline in developing a hydraulic ram pump with better performance associated with its application.